Salt in the Earth - Cengiz Çinku, Mualla; Karabulut, Savas (IntechOpen, 2020)
Salt is a predominant compound for humankind and the earth preserves an important source of this element of life. This book reviews this multi-disciplinary issue in which geoscientists, historians, agriculturalists, medical doctors, and general scientists have been interested in its nature. The authors have provided contributions on the origin and history of salt, intrusion with freshwater effect, its usability as a material, and its role in life. The safety of groundwater resources should be a priority for humanity. Contribution on this important topic is provided by geophysical investigations to characterize saltwater intrusions in aquifers. This book also presents a general overview on salt intake and its role in food and human health. Methods of salt recovery and surface salination as well as its usage in the environment will provide new aspects in earth science.